Pendampingan Pembuatan E-Commerce untuk Memfasilitasi Produk Komoditi Pertanian di Desa Setiris - Riri Oktari Ulma; Yusma Damayanti; Dewi Sri Nurchaini; Yanuar Fitri; Yulismi Yulismi (I-Com: Indonesian Community Journal, 2024)
This community service project focuses on developing an e-commerce platform called Setiris Farmers Market Place, aimed at enhancing the marketing of agricultural products in Setiris Village, Kecamatan Maro Sebo, Kabupaten Muaro Jambi. The initiative involved concept socialization, training in website usage and digital marketing for farmers, and providing ongoing support to optimize the use of technology. Through this project, farmers experienced improved digital literacy and began adopting online marketing strategies more widely. The platform expanded market reach, leading to increased sales and income for local farmers. Moreover, this initiative contributed to local economic development by introducing accessible and relevant technology to support traditional agricultural practices. The success of this project provided valuable insights into how technology can be integrated into the agricultural sector, opening up new opportunities for farmers in the village to access broader markets and improve their livelihoods. Keywords: e-commerce, agricultural marketing, digital literacy, community development, Setiris Village.